Fostering Mathematical Inquiry with Language Independent Board Games - Edwards, Michael Todd; Yang, Zheng; Zeng, Jingyi (Ohio Journal of School Mathematics, 2022)
The authors discuss an approach for engaging students in mathematical problem solving and argumentation in a manner that supports all learners, including those for whom English is a non-native language (i.e., ELLs). Building on the work of Norval and Castaneda (2020), Wanko (2017), and others, the authors engage students in a language-independent game, Where are the Cherries?. English-speaking students learn the rules of the game as they analyze an instructional video in Chinese. Students strengthen their problem solving skills as they develop a greater appreciation of the language challenges that ELL classmates face on a daily basis.